DENEYSEL Dİ-(2-ETİLHEKZİL) FİTALAT (DEHP) ZEHİRLENMESİNİN PREPUBERTAL RATLARDA OLUŞTURDUĞU TESTİKÜLER TOKSİSİTE VE GİNKGO BİLOBA EKSTRAKT 761 (EGB 761)'İN KORUYUCU ETKİSİNİN İNCELENMESİ - AK, TUBA PARLAK (Fırat Üniveristesi, 2012)
Çalışmada; prepubertal gelişim dönemindeki ratlara farklı sürelerde aynı dozda di-(2-etilhekzil) fitalat (DEHP) verilerek oluşturulan testis hasarı üzerine ginkgo biloba ekstrakt 761 (EGb 761)?in koruyucu etkisi mikroskobik ve biyokimyasal olarak incelendi. Bu amaçla:1. Yetmiş iki adet 28 günlük Wistar albino cinsi rat; kontrol, DEHP, DEHP + EGb 761 ve EGb 761 olmak üzere 4 ayrı deney grubuna (n=18) ayrıldı. Çalışmanın 7., 14., ve 28. günlerinde her gruptan 6?şar hayvan dekapite edildi. Hayvanlardan alınan testis dokularından parafin bloklar hazırlanarak 5 ?m kalınlığında seri kesitler alındı. Bu kesitler hematoksilen- eozin (H&E), periyodik asit schiff (PAS) & hematoksilen ve TdTmediated dUTP- digoxigenin Nick End Labeling (TUNEL) yöntemleriyle boyanarak ışık mikroskobunda değerlendirildi. Hayvanlardan alınan doku ve serum örnekleri ise malondialdehit (MDA), glutatyon (GSH), glutatyon peroksidaz (GSH-Px), katalaz (CAT) ve testosteron düzeyleri bakımından biyokimyasal olarak incelendi.2. Kontrole göre DEHP grubunda canlı ağırlık ve testis ağırlıklarının 7. ve 14. günlerde azaldığı; 28. günde ise önceki deney periyotlarına göre arttığı saptandı. DEHP + EGb 761grubunda ise tüm deney periyodu boyunca DEHP grubuna kıyasla artmış olduğu belirlendi.3. Mikroskobik olarak 7. günde DEHP grubunda, tubulus seminiferus kontortus (TSK) çapında ve germinal hücre kalınlığında (GHK) azalma dikkati çekti. TSK?larda dejenerasyon, nekroz ve atrofinin yanı sıra bazal membranda kalınlaşma; germinal hücrelerde ise sayıca azalma, disorganizasyon ve vakuolizasyon gözlenen başlıca bulgular idi. 14. günde gözlenen bulguların 7. gündekiler ile benzer; ancak daha şiddetli olduğu

In this study, the protective effect of ginkgo biloba extract 761 (EGb 761)?s on testicular damage was analyzed microscopically and biochemically by giving the same dose di-(2-ethylhexyl) phthalate (DEHP) to rats in prepubertal developing stages at different times. For this reason: 1.Seventy-two Wistar albino rats of 28 days were divided into four subject groups of control, DEHP, DEHP + EGb 761 and EGb 761. At the 7th,14th and 28th days of the study, 6 animals from each group were decapitated. 5 ?m thickness of serial sections were taken by preparing paraffin blocks from animal?s testicular tissues. These sections were evaluated under a light microscope by staining the methods of hematoxylin- eosin (H&E), periodic acid schiff (PAS) & hematoxylin and TdT- mediated dUTP- digoxigenin Nick End Labeling (TUNEL). Tissue and serum samples taken from animals were analyzed biochemically in terms of malondialdehyde (MDA), glutathione (GSH), glutathione peroxidase (GSH-Px), catalase (CAT) and testosterone levels.2.According to the control, it was determined that live weight and testicular weights decreased in 7th and 14th days but increased in 28th day in terms of the prior experiment periods in DEHP group. Besides, it was found that these values increased in DEHP + EGb 761 group compared to DEHP group throughout the all experimental period.3.Microscopically, it was found that a decrease in the diameter of tubulusseminiferous contortus (TSC) and germinal cell thickness (GCT) in DEHP group. Degeneration, necrosis and atrophy, as well as thickening of the basement membrane in TSC?s and decrease in number, disorganization and vacuolization germinal cells were 4observed. Findings of 14th day were similar to 7th day but more severe. While multinucleated giant cell formations were encountered in TSC?s; the presence ofhyperplasia in Leydig cells drew attention. Findings were also evaluated as more mildly, and even partial regeneration started at 28th day when compared to prior experiment period. An increase in Leydig cell hyperplasia and thickening of the basement membrane was found. The above mentioned findings in DEHP + EGb 761group gradually abated, and dominated by the regeneration throughout the all experimental period.4. According to the evaluations of TUNEL method, while it was found that apoptosis increased in spermatogenic cells at the 7th day, it decreased gradually compared to the previous experiment period at 14th and 28th days in DEHP group. In DEHP + EGb 761 group TUNEL positive cell number gradually decreased throughout the allexperimental period compared to DEHP.5. Biochemically, while a decrease in serum testosterone levels was observed in DEHP group at 7th and 14th days compared to control group; an increase was observed at 28th day compared to previous experiment periods. An increase in MDA, GSH-Px and CAT levels but a decrease in GSH levels were observed in DEHP group throughout the all experimental periods when compared to control group. In DEHP + EGb 761 group, an increase in testosterone and GSH levels but a decrease in MDA, GSH-Px and CAT levels were observed compared to DEHP.In conclusion, it was determined that DEHP is highly toxic to the testis tissue for the application duration and dose and cause to severe structural damage. It was identified that EGb 761 which has antioxidant effect prevents largely this damage.Key Words: Apoptosis, Di-(2-ethylhexyl) phthalate (DEHP), Ginkgo biloba extract 761 (EGb 761), prepubertal rats, testicular toxicity, TdT- mediated dUTPdigoxigenin Nick End Labeling (TUNEL)
Analysis of ginkgo biloba extract 761 (EGb 761)'s protective effect and testicular toxicity of experimental di-(2-ethylhexyl) phthalate (DEHP) poisoning in prepubertal rats
Keywords: Histoloji ve Embriyoloji